If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 117 + -37x Solving 13 + -9x = 117 + -37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37x' to each side of the equation. 13 + -9x + 37x = 117 + -37x + 37x Combine like terms: -9x + 37x = 28x 13 + 28x = 117 + -37x + 37x Combine like terms: -37x + 37x = 0 13 + 28x = 117 + 0 13 + 28x = 117 Add '-13' to each side of the equation. 13 + -13 + 28x = 117 + -13 Combine like terms: 13 + -13 = 0 0 + 28x = 117 + -13 28x = 117 + -13 Combine like terms: 117 + -13 = 104 28x = 104 Divide each side by '28'. x = 3.714285714 Simplifying x = 3.714285714
| -13-8x=8x+19 | | 5(1-x)=0 | | -13-8x=8x | | 4x+11=-22-7x | | 92-3x=3x+8 | | -5-5x=10-10x | | A*A+2A=37250 | | 2a+3b= | | 3x-6y=-20 | | 2x+9y=-9 | | x-6-(x+6)=0 | | 5x+31=13x-33 | | 3x+14=9x-5 | | 2x+33=12x-67 | | 10x-3=5x+17 | | 115-6x=12x+15 | | 8x-8=88 | | 14-9x=58-23x | | 4x-2x-12=0 | | 10x+19=69 | | 2+3(x-1)=x-1 | | 169-6x=4x+19 | | -4-5x=10-7x | | 8x+25=3x+105 | | -10-7x=9x+22 | | 99-6x=12x+17 | | 11=5-4x | | x^4-8x^3+17x^2-1=0 | | 2+8x+1=6x+5 | | 13-7x=177-35x | | 10-10x=215-45x | | -146-10x=8x+16 |